Melodians Takes Pan to Middle East, North Africa - Unknown (Trinidad Guardian)
The globe-trotting BT Melodians Steelband - founded and led by Trinidadian Terrence Noel - was in full attendance in two different countries during April. The first visit (April 18-22) was to Doha, Qatar to entertain guests of the British Ambassador, John Hawkins and then it was on to Morocco, North Africa (April 28-30) to be part of the celebration to mark the wedding of Prince William and Kate, Duchess of Cambridge.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago; Entertainers -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago